2016
DOI: 10.1039/c6cp00756b
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing electrode edge in organic transistors with ultrathin reduced graphene oxide for improving charge injection efficiency

Abstract: Electrode materials and geometry play a crucial role in the charge injection efficiency in organic transistors. Reduced graphene oxide (RGO) electrodes show good compatibility with an organic semiconductor from the standpoint of energy levels and ordered growth of the organic semiconductor, both of which are favourable for charge injection. However, the wide electrode edge (>10 nm) in commonly-used RGO electrodes is generally detrimental to charge injection. In this study, ultrathin (about 3 nm) RGO electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The current on/off ratio of devices is focused on 10 5 , and 30% of transistors are on the order of 10 6 . Our bottom-contact devices with excellent field-effect performance can be attributed to the coplanar configuration that eliminates the electrode step 36 , 37 . As shown in the cross-section image of Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The current on/off ratio of devices is focused on 10 5 , and 30% of transistors are on the order of 10 6 . Our bottom-contact devices with excellent field-effect performance can be attributed to the coplanar configuration that eliminates the electrode step 36 , 37 . As shown in the cross-section image of Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Also, electrode geometry plays an important role on the performance of organic FETs. It was found that 71 the organic FETs with ultrathin RGO electrodes show significantly improved charge injection efficiency compared to those with thick electrodes due to the narrow edges (~3 nm), which may facilitate the diffusion and assembly of organic semiconductors and thus form a uniform semiconductor film across the electrode/channel junction area [288]. As the RGO electrode edge minimizes from 20 to ~3 nm, the width-normalized contact resistance sharply decreases from ~120 to 49.8 kΩ·cm.…”
Section: Field-effect Transistors (Fets)mentioning
confidence: 99%
“…(ii) Outstanding chemical inertness and biocompatibility ensure biosecurity of the prepared wearable and implantable devices, while silver or copper fails in maintaining a long-term stability in atmosphere or complex body fluidic environments . (iii) Compared to nanostructured conductors such as nanowires, nanomeshes, and nanotroughs, Au film possesses a dense and uniform structure resulting in the formation of excellent conductive uniformity and a very smooth surface, which is beneficial to reduce contact resistance between electrode and active materials and further obtain high-performance devices and circuits. (iv) The good mechanical robustness of stretchable Au film allows electrical conductivity to be fully recovered after multiple stretchings, while CNTs always show partial recover after only once stretching . (v) Au film can be easily prepared by vacuum evaporation and can combine with conventional photolithography technology to design high-resolution sophisticated electrode micropatterns, , which is beneficial to realize large-scale high-integration multifunction commercial electronic products.…”
Section: Introductionmentioning
confidence: 99%